Epistemic evaluation of the training and managerial competence development process - Machado, Evelio F. (2015)
This article presents the problem of defining the concept of “competence”, due to it being an integral and complex term that has been applied in many domains as well as in a more general sense for everyday life. However, no doubt, a competence can only be tested and valuated in the practice, and it is a person who becomes competent in a context for a certain function. This is why there are many different conceptions in the literature regarding this issue; it’s a consequence of its imprecise, variable character. However, the position profiles (mainly in educational entities) and the acceptation/ graduation profiles are being more and more frequently established in terms of competences. This paper intends to check what has been valuated and written about the managerial competences training and development regarding the educational field, in order to obtain conclusions regarding its dimension in the school level.